Analysis of the Effect of Deforestation on Soil Erosion in South America: Causal Factors, Impact, and Mitigation Strategie - Minaya Loconi, Maritza Angeli; Velazco Bernal, Pierre Alexander; Polo Herrera, Kelly Milena; Naupari Montenegro, Sara Rita; Díaz Díaz, Marco Antonio (LACCEI, 2025)
Deforestation in South America has significantly contributed to soil erosion, compromising stability, fertility, and water retention capacity. Key drivers such as agricultural expansion, urbanization, indiscriminate logging, and illegal mining have accelerated soil degradation, disrupting hydrological cycles, increasing sediment deposition in water bodies, and leading to biodiversity loss. This study examines the impact of deforestation on soil erosion across Colombia, Argentina, Brazil, Ecuador, Peru, and Chile, while proposing effective mitigation strategies. A systematic literature review was conducted using Scopus, Redalyc, and Google Scholar, employing keywords related to erosion and deforestation. Findings indicate that deforestation has intensified erosion over more than 180 million hectares, resulting in severe socioeconomic consequences, including a 36% reduction in agricultural productivity in Argentina, 46 million tons of sediment accumulation annually in Brazil, and increased vulnerability of rural communities, affecting 40% of Colombia's territory. Among the most effective mitigation strategies identified are the use of geotextiles, minimum tillage, infiltration terraces, and reforestation with native species. Additionally, the implementation of stringent environmental policies and conservation programs has been crucial in mitigating erosion and restoring degraded soils. Adopting these strategies could strengthen ecosystem resilience, reduce rural community vulnerability, and support international commitments on conservation, climate change mitigation, and sustainable development.